2000
DOI: 10.1093/jac/46.6.901
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of meropenem and aminoglycosides on Pseudomonas aeruginosa in vitro

Abstract: To investigate combinations of antibiotics against Pseudomonas aeruginosa, the in vitro effects of combinations of meropenem with each of three aminoglycosides, arbekacin, amikacin and netilmicin, were evaluated using an agar dilution chequerboard technique. The combinations of meropenem and aminoglycosides were effective against almost all P. aeruginosa strains tested, which included meropenem-resistant strains. Increased synergic effects were observed in combinations that included arbekacin or amikacin. None… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 6 publications
1
17
0
2
Order By: Relevance
“…In agreement with the present findings, earlier study observed 58% synergism, 40% additive effect, 2% indifference while combining meropenem with amikacin. 15 Higher synergy (100%) was detected by Le et al 16 by time-kill assay against four Klebsiella pneumonia carbapenemase (KPC) strains. Piperacillin/tazobactam plus amikacin combinatoin showed 80% synergism, 10% additive effect, and 10% indifference in the present study.…”
Section: Discussionmentioning
confidence: 95%
“…In agreement with the present findings, earlier study observed 58% synergism, 40% additive effect, 2% indifference while combining meropenem with amikacin. 15 Higher synergy (100%) was detected by Le et al 16 by time-kill assay against four Klebsiella pneumonia carbapenemase (KPC) strains. Piperacillin/tazobactam plus amikacin combinatoin showed 80% synergism, 10% additive effect, and 10% indifference in the present study.…”
Section: Discussionmentioning
confidence: 95%
“…The issue of synergism against other microorganisms is less clear. Despite the fact that such a synergistic effect was also demonstrated for some strains of Enterobacteriaceae (80,148,219), Pseudomonas aeruginosa (29,56,147,209), staphylococci (33,34,252,310), including methicillin-resistant Staphylococcus aureus (MRSA) (125), and other microorganisms (80), many of these microorganisms were not inhibited by a combination of aminoglycoside and cell wall-active compounds (131,153,245). In a disconcerting development, antagonism between aminoglycosides and ␤-lactams was recently described (135).…”
Section: Antimicrobial Activity and Clinical Indicationsmentioning
confidence: 99%
“…It is reported that the combination of meropenem and aminoglycoside is effective against almost all P. aeruginosa strains which included meropenemresistant strains (21). According to the results of this study aminoglycoside is one of the most effective antibiotics and resistance percentages were decreased.…”
Section: öZetmentioning
confidence: 57%